1989
DOI: 10.1111/j.1365-277x.1989.tb00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Selenium‐iron interaction in young women with low selenium status

Abstract: The effect of inorganic selenium (Se) supplementation on iron status and iron supplementation on selenium status was investigated in Finnish female students (=33). The students were divided into three groups and supplemented daily for four weeks either with 150 μg Se as sodium selenate, or 120 mg Fe as ferrous sulfate, or 120 mg Fe as ferrous sulfate and 150 μg Se as sodium selenate. Plasma selenium level was used as an indicator of body selenium status. Haematocrit and serum ferritin concentrations were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…On the contrary, in young women with prelatent iron de ciency without manifest anemia, serum concentrations of Se have not been found to differ signi cantly from those of controls [30]. No relationship has been observed between serum concentrations of Se and parameters assessing different aspects of iron metabolism, such as serum levels of ferritin, Fe, and TIBC, in both subjects with normal Fe status and patients with IDA [26,27,31].…”
Section: Interactions Between Selenium and Ironmentioning
confidence: 90%
See 2 more Smart Citations
“…On the contrary, in young women with prelatent iron de ciency without manifest anemia, serum concentrations of Se have not been found to differ signi cantly from those of controls [30]. No relationship has been observed between serum concentrations of Se and parameters assessing different aspects of iron metabolism, such as serum levels of ferritin, Fe, and TIBC, in both subjects with normal Fe status and patients with IDA [26,27,31].…”
Section: Interactions Between Selenium and Ironmentioning
confidence: 90%
“…Morris et al (1984) have reported a positive in uence of Se supplementation on Hb concentration and Hct in cattle [16]. Conversely, studies by other research groups have not shown signi cant impact of Se supplementation on the values of Hb concentration, Hct, and serum ferritin [18,31].…”
Section: Interactions Between Selenium and Ironmentioning
confidence: 97%
See 1 more Smart Citation